1999
DOI: 10.1159/000007160
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of Ampicillin- Resistant, Non-Beta-Lactamase-Producing Strains of <i>Haemophilus influenzae</i> in Children in Japan

Abstract: Among Haemophilus influenzae isolated from children with respiratory tract infections, the evolution of ampicillin resistance was investigated during 1996 and 1997 in Japan. β-Lactamase production was assessed and minimum inhibitory concentrations (MICs) of eight antimicrobial agents were determined using a broth microdilution method in Mueller-Hinton-lysed horse blood medium. Of 74 H. influenzae, 11 strains (14.9%) produce β-lactamase and were thus highly resistant to ampicillin (MIC of >4.0 µg/ ml). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 21 publications
1
38
0
1
Order By: Relevance
“…Interestingly, in the United States and Europe, the BLNAR strains were uncommon and represented less than 1 to 2% of H. influenzae strains until the early 1990s, with their prevalence gradually increasing from 2.5% in 1994 to 10.1% 1995 (4)(5)(6)16). In Japan, the BLNAR strains were not identified before 1984 and then had a prevalence of only 2.1% in 1988 and 5.0% in 1991 (32). The strains with MICs for AMP of 1.0 g/ml then increased from 23.1% to 37.8% from 1996 to 1999 (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in the United States and Europe, the BLNAR strains were uncommon and represented less than 1 to 2% of H. influenzae strains until the early 1990s, with their prevalence gradually increasing from 2.5% in 1994 to 10.1% 1995 (4)(5)(6)16). In Japan, the BLNAR strains were not identified before 1984 and then had a prevalence of only 2.1% in 1988 and 5.0% in 1991 (32). The strains with MICs for AMP of 1.0 g/ml then increased from 23.1% to 37.8% from 1996 to 1999 (32).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the BLNAR strains were not identified before 1984 and then had a prevalence of only 2.1% in 1988 and 5.0% in 1991 (32). The strains with MICs for AMP of 1.0 g/ml then increased from 23.1% to 37.8% from 1996 to 1999 (32). Furthermore, a prospective prevalence study in Japan in 1999 showed that 55.1% of the H. influenzae strains were BLNAS, 3% were BLPAR, 26.4% were intermediateresistant strains, and 13.2% were BLNAR (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are many types of oral antimicrobial agents such as ␤-lactams, fluoroquinolones, and penems with broad antibacterial activities. Recently, there has been an increase in the incidence of community-acquired respiratory tract infections caused by penicillin-resistant Streptococcus pneumoniae, penicillinase-producing Haemophilus influenzae, and ␤-lactamase-nonproducing ampicillin-resistant H. influenzae (3,13,18). In addition, the incidence of infections caused by fluoroquinolone-resistant organisms also seems to have increased (1,5,14).…”
Section: L-084 (A Prodrug Of Ljc 11036 [L-036]) Is a New Oral Carbapmentioning
confidence: 99%
“…H. influenzae is known to acquire antibiotic resistance by two different mechanisms: the production of ␤-lactamases (TEM-1 or ROB-1 type) (19,41) and mutations in the penicillin-binding protein (PBP) gene. In Japan, the prevalence of ␤-lactamase-positive ampicillin (AMP)-resistant (BLPAR) H. influenzae is not high, with such isolates constituting less than 6% of all clinical H. influenzae isolates (11,13,34), while recent studies have shown that H. influenzae strains with mutations in the PBP gene, such as ␤-lactamase-negative AMP-resistant (BLNAR) H. influenzae and ␤-lactamase-positive amoxicillin-clavulanic acid-resistant (BLPACR) H. influenzae, are increasing (12,30). Ubukata et al (37,38) have discovered several mutations in the ftsI gene, which encodes PBP 3, in clinically isolated H. influenzae strains.…”
mentioning
confidence: 99%